Covenantal leadership and the psychological contract: moral insights for the modern leader. Issue 10 (14th November 2016) - Caldwell, Cam; Hasan, Zuhair
Abstract : Purpose: Research confirms that leaders continue to struggle in earning followers' trust, commitment, and organizational citizenship. The purpose of this paper is to explain the importance of the relationship between leader and followers as a covenant and to identify five roles of the leader that are necessary to be effective in creating the required relationship with followers to earn their trust in an increasingly competitive and complex market. Design/methodology/approach: The approach of this paper is to present a summary of the nature of psychological contracts and to identify seven testable propositions about covenantal leadership and its ability to build trust and honor duties implied in psychological contracts of employees. Findings: The authors explain how the five roles of the covenantal leader increase trust and examine each of these roles in identifying the importance of covenantal leadership in serving the modern leader. Research limitations/implications: This research reaffirms the importance of leaders understanding the often unarticulated perceptions of their employees in imposing moral duties and obligations on leaders and organizations. Practical implications: The practical value of this paper lies in its insights about the importance of leaders understanding and honoring implied as well as stated duties, and in recognizing employee perceptions about their needs and the often unaddressed obligations of leaders and organizations. Social implications: The underlying assumptions of this paper are that leaders who seek to create greater commitment and higher performance can do so by seeking out, understanding, and honoring the implicit and explicit assumptions and expectations of their employees. Originality/value: Covenantal leadership is a relatively new leadership model introduced by Moses Pava (2003) and the five roles of covenantal leadership have rarely been addressed as a leadership perspective in the scholarly and practitioner literature.